Involvement of Nrf2-HO-1/JNK-Erk Signaling Pathways in Aconitine-Induced Developmental Toxicity, Oxidative Stress, and ROS-Mitochondrial Apoptosis in Zebrafish Embryos - Xia, Qing; Gao, Shuo; Rapael Gnanamuthu, Samuel Rajendran; Zhuang, Kaiyan; Song, Zhenzhen; Zhang, Yun; Wang, Xue; Tu, Pengfei; Li, Jianheng; Liu, Kechun (Frontiers in Pharmacology, 2021)
Aconitine (AC), one of the bioactive diterpenoid alkaloid extracted from aconitum plants, is widely used in traditional herbal medicine to treat various diseases. Emerging evidence indicates that AC has attracted great interest for their wide cardiotoxicity and neurotoxicity. However, the toxic effects of AC on embryonic development and their underlying mechanisms remain unclear. Here, a developmental toxicity assay of AC was performed on zebrafish embryos and its underlying mechanisms were discussed. Our results showed that AC treatment affected the development of the heart, liver, and nervous system. Especially, a high dose of AC (7.27 and 8.23 μM) exposure resulted in malformations, including reduced body length, curved body shape, pericardial edema, yolk retention, swim bladder and brain deficiency, and loss of dopaminergic neurons. AC exposure caused a deficient cardiovascular system with cardiac dysfunctions, increased heart rates, and reduced swimming behavior of 96 hpf embryos. AC treatment significantly increased the level of reactive oxygen species in zebrafish embryos and triggered cell apoptosis in the heart and brain regions. Besides, oxidative stress was evidenced by decreased levels of T-SOD activity, by increased lipid peroxidation, and by the expression levels of oxidative stress-related genes. The expression levels of oxidative stress-related genes (Nrf2, HO-1, Cat, and Sod-1), Erk1/2 and Bcl-2 were significantly down-regulated. The expression levels of JNK and mitochondrial apoptosis-related genes (Bad, Bax, Cyto C, Casp-9, and Casp-3) were significantly up-regulated. In conclusion, our results provided preliminary evidence that AC induced developmental toxicity in zebrafish through ROS-medicated mitochondrial apoptosis involving Nrf2/HO-1 and JNK/Erk pathways.